Chiral Resolution, Absolute Configuration Assignment, and Genotoxicity Evaluation of Racemic 3, 4-Dihydroquinazoline as a Novel Anticancer Agent. (25th October 2021) - Ahn, Junseong; Ko, Dohyeong; Yang, Seyoung; Moon, Kwang H.; Woo, Jiwon; Yoo, Ho; Ahn, Joohoon; Lee, Jeong H.; Chung, Kyung S.; Lee, Kyung-T.; Lee, Jae Y.
Abstract : If a new drug candidate will be a mixture of enantiomers, both enantiomers should be separately studied for at least latent genotoxicity as early as possible since the thalidomide tragedy. Our group has recently reported that KCP-10043F (OZ-001 ) as a racemate (±)-3, 4-dihydroquinazoline derivative strongly represses the proliferation of human A549 lung cancer cells by caspase-mediated apoptosis via STAT3 inactivation. To investigate the possible teratological effects of the two enantiomers of a racemic KCP-10043F, therefore chiral resolution of (±)-KCP-10043F was performed and subsequently followed by a series of chemical processes to afford the corresponding chiral diastereomers. By using 1 H NMR anisotropy method, the absolute configuration (+)-KCP-10043F and (− )-KCP-10043F could be assigned as S and R configuration, respectively. The bacterial reverse mutation test (Ames test) for racemate (±)-KCP-10043F and its two enantiomers exhibited that all three stereoisomers were found to be nongenotoxic against five bacterial strains with/without metabolic activation. In addition, ( R )-(− )-KCP-10043F displayed almost equal anticancer activity to ( S )-(+ )-KCP-10043F against three cancer cell lines. Based on these overall results, racemate KCP-10043F (OZ-001) could be used for our ongoing preclinical and clinical studies without the expensive asymmetric process and/or chiral separation.